The Gut Microbiome Associates with Immune Checkpoint Inhibition Outcomes in Patients with Advanced Non-Small Cell Lung Cancer - Hakozaki, Taiki; Richard, Corentin; Elkrief, Arielle; Hosomi, Yukio; Benlaïfaoui, Myriam; Mimpen, Iris; Terrisse, Safae; Derosa, Lisa; Zitvogel, Laurence; Routy, Bertrand; Okuma, Yusuke (Cancer immunology research, 2020)
The gut microbiome (GM) plays an important role in shaping systemic immune responses and influences immune checkpoint inhibitor (ICI) efficacy. Antibiotics worsen clinical outcomes in patients receiving ICI. However, whether GM profiling and baseline antibiotic can be a biomarker of ICI efficacy in advanced non-small cell lung cancer (NSCLC) remains unknown. We prospectively collected baseline (pre-ICI) fecal samples and clinical data of 70 Japanese patients suffering from advanced NSCLC and treated them with anti-PD-1/PD-L1 antibodies as a first-line or treatment-refractory therapy. We performed 16S rRNA V3-V4 sequencing of gene amplicons of fecal samples, and bacteria diversity and differential abundance analysis was performed. The clinical endpoints were objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and immune-related adverse events (irAE). ORR was 34%, and median PFS and OS were 5.2 and 16.2 months, respectively. Patients who received pre-ICI antibiotic had lower alpha diversity at baseline and underrepresentation of UCG 13 and When analyzing antibiotic-free patients, alpha diversity correlated with OS. In addition, UCG 13 and were enriched in patients with favorable ORR and PFS >6 months. UCG 13 was enriched in patients with OS >12 months. GM differences were observed between patients who experienced low- versus high-grade irAE. We demonstrated the negative influence of antibiotic on the GM composition and identified the bacteria repertoire in patients experiencing favorable responses to ICI. .